Relationship between Interest and Independence in Learning toward Physics Learning Outcomes: A Case of SMA Negeri 2 Gowa - Asmar, Muhammad Alwi; Ali, M Sidin; Arafah, Kaharuddin (Jurnal Pendidikan MIPA, 2023)
This research is survey research that aims to determine the relationship between (1) interest in learning with learning outcomes of physics, (2) independent learning with learning outcomes of physics, (3) interest in learning and independent learning together with learning outcomes of physics, (4) interest in learning with physics learning outcomes if it controls learning independence and (5) independent learning with physics learning outcomes if it controls learning interest. The research sample of 110 students was obtained through a multistage random sampling technique. Data collection was carried out through questionnaires and tests. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the descriptive statistical analysis showed that the average score of learning interest was in the high category, learning independence was in the high category, and physics learning outcomes were in a low category. For inferential statistics, there is a positive and significant relationship between learning interest and physics learning outcomes, there is an insignificant positive relationship between learning independence and physics learning outcomes, and there is a positive but not significant relationship between learning interest and learning independence together with learning outcomes physics, there is a positive but not significant relationship between learning interest and physics learning outcomes if controlling for independent learning, there is no positive and significant relationship between independent learning and physics learning outcomes if controlling for interest in studying physics for Students of SMA Negeri 2 Gowa.Keywords: learning outcomes of physics, independent learning, interest in learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp59-71